WEB-BASED APPLICATION WITH SDLC WATERFALL METHOD ON POPULATION ADMINISTRATION AND REGISTRATION INFORMATION SYSTEM (CASE STUDY: KARANGKLESEM VILLAGE, PURWOKERTO) - Teguh Rijanandi; Tri Dimas Cipto Satrio Wibowo; Ikadhanny Yudyan Pratama; Faisal Dharma Adhinata; Annisaa Utami (Jurnal Teknik Informatika (Jutif), 2022)
Based on research conducted in one of the Neighborhood Associations (RT) in Karangklesem Village, South Purwokerto found that a population administration and recording system did not use computer technology. Our authors created a web-based village information system design using CodeIgniter based on this research. The software development method used is the Software Development Life Cycle (SDLC) Waterfall method. With the software that we have developed, it is hoped to help facilitate all administrative matters and village records that are currently still manual. The design we made uses the PHP programming language version 7.4 CodeIgniter framework with a MySQL database. We hope that this system design can reduce human errors in recording administration.